Consumer awareness, perception, attitude and willingness-to-pay for organic rice in Klang valley, Malaysia - Ibitoye, Olusola Olugbenga (2015)
Consumers are now aware about their health, food safety and environment as they are worried about the presence of the negative consequences of chemical residues occasioned by conventional production methods. People are now willing to pay increasing premium price for organic product since its production process is without the use of chemical inputs. As a result, markets for organic products are rapidly increasing as it is recognized as one of the contributors to a healthy and sustainable lifestyle. Although, the demand for organic food in Malaysia is growing, local supply is not enough to meet up with this demand. Despite this shortfall, it is been foreseen that organic food demand would continue to rise in Malaysia as consumers become more health and environmentally conscious. One of these organic food is organic rice. Demand for organic rice consumption is reported to have increased in Malaysia and there is a need to understand consumers‟ behaviour toward organic rice. Hence, the study investigated Malaysian consumers‟ awareness, factors influencing their purchase decision and willingness-to-pay (WTP) or no willingness-to-pay (nWTP) towards organic rice. The sample size was 834 respondents obtained from well completed structured questionnaires. Survey was done using primary data collected through mall intercept technique from selected shopping malls in Klang Valley. The study was conducted in Klang Valley because of its features of varying socio-demographic characteristics among potential consumers. The questionnaire was classified into four sections:Section 1 was based on questions related to awareness and attitudinal characteristics of respondents. Section 2 asked questions related to perception of respondents while section 3 attempted to understand respondents‟ WTP and to determine their percentage premium price WTP responses by bid value for organic rice. Finally, section 4 was on information to determine respondents‟ socio-demographic characteristics. Descriptive analysis, cross-tabulation technique using chi-square analysis, correlation analysis,factor analysis, binary logistic regression and Contingent Valuation Method (CVM) were employed in the analysis of the data. The result revealed majority of respondents had heard about organic rice with varying levels of awareness. Majority of respondents indicated plan to consume organic rice in future. Findings showed awareness dependent on gender, race and education of respondents. Majority of the respondents perceived organic rice as healthier, followed by more expensive, safer to consume and environmental friendly. Based on factor analysis, four factors were identified as influencing intention to purchase (ITP) organic rice namely: Institution intervention, knowledge and awareness, market, and packaging. Binary logistic regression was employed to predict which mostly impacted on the likelihood of respondents‟ ITP among the four factors. Of these four factors,three significantly predicted ITP. The analysis depicted that Market had the highest prediction on ITP followed by Institution Intervention and Packaging respectively. Binary logistic regression also used to examine the effect of socio-demographic characteristics on the likelihood of respondents‟ WTP or nWTP of organic rice. Research findings revealed some of the parameters made a unique statistically significant contribution in predicting respondents‟ WTP towards organic rice. They were age (40-49yrs, 50-59yrs, >60yrs), gender, race (Malay and Chinese), and monthly household income categories (except RM2001-RM4000 income category). This implies that potential consumers with these statistically significant socio-demographic profiles could be targeted by marketers as these identified socio-demographic profiles showed statistically significant probability or likelihood of increasing respondents‟ WTP towards organic rice.